Penerapan Metode Suzuki Dalam Pembelajaran Biola Di Gilang Ramadhan Studio Band Padang - Rahma Ramadhani; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2021)
This study aims to determine how the application of Suzuki method is in violin learning at Gilang Ramadhan Studio Band Padang. This research belongs to a descriptive research which produces qualitative data. The data were obtained during the learning process through interviews conducted to violin instructors at Gilang Ramadhan Studio Band (GRSB) Padang, as well as documentation containing photos during the violin learning process at Gilang Ramadhan Studio Band (GRSB) Padang. Based on the results, the use of Suzuki method in the violin learning process at Gilang Ramadhan Studio Band has not been fully applied. This can be seen in the implementation of learning where there are no group games or group exercises, and there is no CD playing so that it causes the violin learning process to be hampered. Some of the Suzuki method have been applied in the violin learning process at Gilang Ramadhan Studio Band (GRSB) Padang. These include giving music education starting at an early age, rehearsing song material repeatedly, listening to music before playing it, and reading block notation using fingers.